Case Report: Concurrent Occurrence of Abdominal Double Expressor Lymphoma and Jejunum Follicular Lymphoma - Takada, Ryutaro; Watanabe, Tomohiro; Sekai, Ikue; Yoshikawa, Keisuke; Hara, Akane; Otsuka, Yasuo; Yoshikawa, Tomoe; Kamata, Ken; Minaga, Kosuke; Komeda, Yoriaki; Chikugo, Takaaki; Arai, Yasuyuki; et al. (Frontiers in Oncology, 2021)
Double expressor lymphoma (DEL), defined as overexpression of BCL2 and MYC, is an aggressive subtype of diffuse large B cell lymphoma (DLBCL). Here we report a case of a 64-year-old female diagnosed with abdominal DEL transformed from jejunum follicular lymphoma (FL). 18F-fluorodeoxyglucose (FDG)-positron emission tomography showed diffuse accumulation of FDG into the peritoneum and small bowel wall. Double balloon-assisted enteroscopy revealed whitish submucosal tumors in the proximal jejunum. Aggregation of atypical lymphocytes positive for CD20, CD79a, and BCL2 was seen in the jejunal biopsy samples. These atypical lymphocytes were monoclonal since cell surface expression of Ig light chains was limited to  chain by flow-cytometry. Thus, immunohistochemical and flowcytometric analyses data were consistent with FL of the jejunum. Neoplastic lymphocytes obtained from ascites were positive for CD10, CD20, CD79a, BCL2, and BCL6. Fluorescence in situ hybridization (FISH) showed formation of BCL2/IgH fusion gene and extra copies of MYC, the former of which is a characteristic chromosomal abnormality of FL. These genetic alterations and protein expression profiles of ascitic fluid cells were consistent with those of DEL transformed from FL. Given that a significant population of patients with indolent FL of the gastrointestinal tract developed into aggressive DLBCL, it is likely that primary FL of the jejunum transformed into the abdominal aggressive DEL in this case. This case is unique in that concurrent occurrence of FL and DEL was confirmed by immunohistochemical and FISH analyses and that abdominal DEL transformed from jejunal FL was highly suspected.